2016
DOI: 10.1007/s00259-016-3457-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased in vivo availability of the cannabinoid type 2 receptor in Alzheimer’s disease

Abstract: Kinetic modelling of [C]NE40 is possible with a two-tissue reversible model. In contrast to preclinical and post-mortem data, [C]NE40 PET shows lower CBR availability in vivo in AD patients, with no relationship to Aβ plaques. A possible explanation for these findings is that [C]NE40 binds to CBR with lower affinity and/or selectivity than to CBR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 42 publications
1
63
0
1
Order By: Relevance
“…Different from the expected findings, a recent 11 C-NE40 PET study has shown no in vivo CB 2 R upregulation in AD patients and no regional co-localization to Aβ deposits [70]. The authors thus argued for a possible lower affinity of the radioligand ( 11 C-NE40) to CB 2 R [70].…”
Section: Pet Molecular Imaging Of Neuroinflammationmentioning
confidence: 79%
See 1 more Smart Citation
“…Different from the expected findings, a recent 11 C-NE40 PET study has shown no in vivo CB 2 R upregulation in AD patients and no regional co-localization to Aβ deposits [70]. The authors thus argued for a possible lower affinity of the radioligand ( 11 C-NE40) to CB 2 R [70].…”
Section: Pet Molecular Imaging Of Neuroinflammationmentioning
confidence: 79%
“…The authors thus argued for a possible lower affinity of the radioligand ( 11 C-NE40) to CB 2 R [70]. A pilot PET study with 11 C-radiolabeled AA showed in few AD patients a widely elevated tracer uptake in different neocortical regions [71].…”
Section: Pet Molecular Imaging Of Neuroinflammationmentioning
confidence: 99%
“…Further confirmation of the in vivo binding of [ 11 C]NE40 to CB2 was demonstrated in a rat which was sterotactically injected into the right striatum with an adeno‐associated viral vector encoding human CB2 with a point mutation . Based on these encouraging preclinical results and the fact that [ 11 C]NE40 is selective over other 51 different targets and has no toxicological effects in Wistar rats, clinical studies were performed in 6 healthy Caucasian male volunteers and AD patients . Whole‐body PET imaging in the healthy volunteers showed (1) high uptake in liver and intestine, suggesting the hepatobiliary pathway elimination; (2) stable standardized uptake value in the spleen over time due to the specific binding to the CB2 receptors constitutively expressed in this organ; and (3) slight brain uptake and moderately fast washout, in accordance with the low expression of CB2 in healthy brain .…”
Section: Cb2 Radioligands For Pet Imagingmentioning
confidence: 89%
“…Structures of compounds A , [ 11 C]A‐836339 (Yao et al, Horti et al, Savonenko et al, and Pottier et al) and [ 18 F]1 (Moldovan et al); B , [ 11 C]NE40 (Evens et al, Ahmad et al, and Vandeputte et al) and [ 11 C]KP23 (Mu et al); C , [ 11 C]KD2 (Mu et al), [ 11 C]RS‐016 (Slavik et al and Meletta et al), and [ 18 F]RS‐126 (Slavik et al); D , RSR‐056 (Slavik et al); E , [ 18 F]‐ d 2 ‐2 (Hortala et al); F , [ 18 F]3 (Yrjölä et al)…”
Section: Cb2 Radioligands For Pet Imagingmentioning
confidence: 99%
“…CB2, an alternative membrane marker of activated microglial cells, is currently regarded as a critical protein which triggers multiple brain pathophysiological events involved in synaptic plasticity and neuroprotection (Chiurchiù et al, 2015). Several lines of evidence have offered new perspectives on the possible involvement of CB2 signaling in brain and spinal cord traumatic injury, as well as in several neurodegenerative disorders, including AD (Ahmad et al, 2016;Bisogno et al, 2016). These studies support the possibility that CB2 is part of a protective mechanism that is both acutely and chronically activated during neuropathology.…”
Section: Discussionmentioning
confidence: 99%